1994
DOI: 10.1901/jaba.1994.27-301
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Fading as Treatment for Obscenity in a Brain‐injured Adult

Abstract: Obscene verbalizations of a person with traumatic brain injury were treated using stimulus fading as the singular form of intervention. Results of a functional assessment revealed that obscenity was maintained by negative reinforcement. Stimulus fading (initial elimination of instructional demands followed by their gradual reintroduction) produced immediate and substantial reductions in obscenity that were maintained as the frequency of demands increased to baseline levels. Potential applications of the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 11 publications
4
33
0
Order By: Relevance
“…R. Dixon et al et al, 2001;Wilder et al, 2001) and extend these findings beyond the single case study previously reported in the brain injury population (Pace et al, 1994). A clear function for inappropriate verbal behavior was found for each of our participants, and in two of our four cases it was not attention maintained.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…R. Dixon et al et al, 2001;Wilder et al, 2001) and extend these findings beyond the single case study previously reported in the brain injury population (Pace et al, 1994). A clear function for inappropriate verbal behavior was found for each of our participants, and in two of our four cases it was not attention maintained.…”
supporting
confidence: 85%
“…Interestingly, in all of these studies, inappropriate verbal behavior was maintained by attention from a caregiver. The only exceptions of participants' verbal behavior not being solely under the control of attention that have been published in the literature were one elderly participant in the Buchanan and Fisher (2002) research, whose behavior appeared to be controlled by both attention and sensory stimulation, and one participant with brain injury investigated by Pace, Ivancic, and Jefferson (1994), whose behavior was controlled by escape from demands. It remains to be seen whether verbal behavior displayed by clinical populations often serves non-attentionbased functions, and whether these functions can be detected via the functional analysis technology of Iwata et al (1982Iwata et al ( /1994.…”
Section: Introductionmentioning
confidence: 99%
“…The primary treatment, extinction combined with stimulus fading, was based on procedures described in a number of previous reports (e.g., Pace, Ivancic, & Jefferson, 1994;Pace et al, 1993;Zarcone et al, 1993); however, the stimuli used during treatment were unusual. During the course of Sarah's treatment, we observed a problem also noted by Zarcone et al (1994), in that the stimulus fading procedure was unsuccessful in reaching the end-oftreatment criterion.…”
Section: Resultsmentioning
confidence: 99%
“…Related interventions indude altering some feature of the task situation to reduce its aversive characteristics (Pace, Ivancic, & Jefferson, 1994;Weeks & Gaylord-Ross, 1981;Zarcone, Iwata, Smith, Mazaleski, & Lerman, 1994) or strengthening alternative escape behaviors through negative reinforcement (Carr & Durand, 1985;Steege et al, 1990). All of these approaches are based on direct modification of the behavior's maintaining contingency or its establishing operation (Michael, 1982(Michael, , 1993).…”
mentioning
confidence: 99%